The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1997
DOI: 10.1046/j.1471-4159.1997.69031161.x
|View full text |Cite
|
Sign up to set email alerts
|

The Lipid Peroxidation Product, 4‐Hydroxy‐2‐trans‐Nonenal, Alters the Conformation of Cortical Synaptosomal Membrane Proteins

Abstract: Alzheimer's disease (AD) is widely held to be a disorder associated with oxidative stress due, in part, to the membrane action of amyloid~3-peptide (A/3). A~-associated free radicals cause lipid peroxidation, a major product of which is 4-hydroxy-2-trans-nonenal (HNE). We determined whether HNE would alter the conformation of synaptosomal membrane proteins, which might be related to the known neurotoxicity of A~3and HNE. Electron paramagnetic resonance spectroscopy, using a protein-specific spin label, MAL-6 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
137
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 253 publications
(146 citation statements)
references
References 44 publications
4
137
2
Order By: Relevance
“…24) From these findings, therefore, it is suggested that the lipid fluidity at the membrane surface decreased by modification of the synaptosomes with HNE. This finding is not consistent with the reports by Subramanian et al 25) and Buko et al, 26) in which they reported that modification of synaptosomal membranes 25) and liver plasma membranes 26) with HNE caused an increased lipid fluidity of the membranes.…”
Section: Discussioncontrasting
confidence: 85%
“…24) From these findings, therefore, it is suggested that the lipid fluidity at the membrane surface decreased by modification of the synaptosomes with HNE. This finding is not consistent with the reports by Subramanian et al 25) and Buko et al, 26) in which they reported that modification of synaptosomal membranes 25) and liver plasma membranes 26) with HNE caused an increased lipid fluidity of the membranes.…”
Section: Discussioncontrasting
confidence: 85%
“…Oxidatively modified proteins are generally dysfunctional, losing catalytic or structural integrity (29,51,52). Oxidative damage to proteins is of importance in explaining metabolic dysfunctions associated to oxidative stress-mediated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Through hydration, the C-O bond breaks, resulting in 4-hydroxy-2-nonenal. As noted, once formed, HNE can covalently attach to proteins by Michael addition, which alters protein structure (361) and causes a loss of protein function and activity (139).…”
Section: Hne Adduction To Proteinsmentioning
confidence: 93%
“…Protein-bound HNE in brain and progression of Alzheimer's disease. As just discussed, HNE is a reactive product of lipid peroxidation, and this a,b-unsaturated alkenal binds to Cys, His, or Lys residues of proteins, thereby changing the conformation and function of proteins (66,79,139,187,361). In AD, HNE has been found to be significantly elevated in AD brain, plasma, and CSF (187,238,297,348).…”
Section: Ead Carbonylated Proteinsmentioning
confidence: 97%